2018
DOI: 10.2147/copd.s154539
|View full text |Cite
|
Sign up to set email alerts
|

Description of nighttime cough epochs in patients with stable COPD GOLD II–IV

Abstract: PurposeChronic cough is one of the main symptoms of COPD. Ambulatory objective monitoring provides novel insights into the determinants and characteristics of nighttime cough in COPD.Materials and methodsNighttime cough was monitored objectively by LEOSound lung sound monitor in patients with stable COPD II–IV. In 30 patients, with 10 patients in each stage group, nighttime cough was analyzed for epoch frequency, epoch severity (epoch length and coughs per epoch), and pattern (productive or nonproductive).Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…The LEOSound® Monitor has been studied in chronic obstructive pulmonary disease [9, 10], in children and adults with asthma [11], and in patients with obstructive sleep apnea [12], where it was used to monitor cough, wheeze, and obstructive sleep apneas. The LEOSound® Monitor is a battery-operated device that electronically records breath and lung sounds using four microphones.…”
Section: Methodsmentioning
confidence: 99%
“…The LEOSound® Monitor has been studied in chronic obstructive pulmonary disease [9, 10], in children and adults with asthma [11], and in patients with obstructive sleep apnea [12], where it was used to monitor cough, wheeze, and obstructive sleep apneas. The LEOSound® Monitor is a battery-operated device that electronically records breath and lung sounds using four microphones.…”
Section: Methodsmentioning
confidence: 99%
“…Wheezing is a sign of an uncontrolled level of asthma. Automatic detection and classification of cough and wheezing is useful in assisting physicians in the diagnosis and monitoring of acute and chronic respiratory diseases such as asthma, acute bronchitis and COPD [11,12,[16][17][18]. Grading of asthma control necessitates specifying the rate of [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although new technology has been developed to monitor coughing during sleep in patients with COPD, more studies are needed to validate the results. Fisher et al 46 , using a LEOSound lung sound monitor, showed that coughing events were found in all the 30 COPD studied, but that most of the coughing periods were non-productive. This correlates with the fact that productive cough is predominantly found in the early morning after getting up from bed 47 .…”
Section: Methods To Assess and Measure Symptom Variabilitymentioning
confidence: 99%